CD38 knockout natural killer cells expressing an affinity optimized CD38 chimeric antigen receptor successfully target acute myeloid leukemia with reduced effector cell fratricide - Gurney, Mark; Stikvoort, Arwen; Nolan, Emma; Kirkham-McCarthy, Lucy; Khoruzhenko, Stanislav; Shivakumar, Rama; Zweegman, Sonja; Van de Donk, Niels W.C.J.; Mutis, Tuna; Szegezdi, Eva; Sarkar, Subhashis; O’Dwyer, Michael (Haematologica (Roma), 2022)
There is a strong biological rationale for the augmentation of allogeneic natural killer (NK) cell therapies with a chimeric antigen receptor (CAR) to enhance acute myeloid leukemia (AML) targeting. CD38 is an established immunotherapeutic target in multiple myeloma and under investigation as a target antigen in AML. CD38 expression on NK cells and its further induction during ex vivo NK cell expansion represent barriers to the development of a CD38 CAR-NK cell therapy. We set out to develop a CD38 CAR-NK cell therapy for AML, first by using an NK cell line which has low baseline CD38 expression and subsequently NK cells expanded from healthy donors. To overcome anticipated fratricide due to NK cell CD38 expression when using primary expanded NK cells, we applied CRISPR/Cas9 genome editing to disrupt the CD38 gene during expansion, achieving a mean knockdown efficiency of 84%. The resulting CD38 knockdown expanded NK cells, after expression of an affinity optimized CD38 CAR, showed reduced NK-cell fratricide and an enhanced ability to target primary AML blasts. Furthermore, the cytotoxic potential of CD38 CAR-NK cells was augmented by pretreatment of the AML cells with all-trans retinoic acid which drove enhanced CD38 expression, offering a rational combination therapy. These findings support the further investigation of CD38 knockdown - CD38 CAR-NK cells as a viable immunotherapeutic approach to the treatment of AML.